QUO VADIS: STATUS JABATAN DAN SISTEM KARIR KEPANITERAAN PERADILAN - Suhariyanto, Budi (Jurnal Hukum dan Peradilan, 2014)
Normatively, judicial registrar status is set differently. While explicity defined as a functional, but without the credit and judicial office. Functional qualification held judicial registrar existence is synchronizedwith the structural position of the promotion system and regular. A clerk on the supreme of court must be a judges. So that the clerk have a career at the highest level only appellate court registry. The supreme of court regulation drafting that gaves the registrar portion to career clerk, then enactment of civilian state apparatus regulation get the civil servants functional oriented. It is necessary to evaluate the official status to career system. On the ius constituendum, registrar as the special functional need to be considered. Keyword: function, career, registrar